Comparison of Antibacterial Activity and Wound Healing in a Superficial Abrasion Mouse Model of Staphylococcus aureus Skin Infection Using Photodynamic Therapy Based on Methylene Blue or Mupirocin or Both - Pérez, Montserrat; Robres, Pilar; Moreno, Bernardino; Bolea, Rosa; Verde, Maria T.; Pérez-Laguna, Vanesa; Aspiroz, Carmen; Gilaberte, Yolanda; Rezusta, Antonio (Frontiers in Medicine, 2021)
Background: Antibiotic resistance and impaired wound healing are major concerns in S. aureus superficial skin infections, and new therapies are needed. Antimicrobial photodynamic therapy (aPDT) is a new therapeutic approach for infections, but it also improves healing in many wound models. Objective: To compare the antimicrobial activity and the effects on wound healing of aPDT based on Methylene Blue (MB-aPDT) with mupirocin treatment, either alone or in combination, in superficial skin wounds of S. aureus-infected mice. Additionally, to evaluate the clinical, microbiological and cosmetic effects on wound healing. Materials and methods: A superficial skin infection model of S. aureus was established in SKH-1 mice. Infected wounds were treated with MB-aPDT, MB-aPDT with a daily topical mupirocin or only with mupirocin. No treatment was carried out in control animals. Daily clinical and microbiological examinations were performed until complete clinical wound healing. Histopathological studies and statistical analysis were performed at the end of the study. Results: MB-aPDT treatment induced the best wound healing compared to mupirocin alone or to mupirocin plus MB-aPDT. Superficial contraction at 24h and a greater reduction in size at 48h, quicker detachment of the crust, less scaling and absence of scars were observed. Histopathological studies correlated with clinical and gross findings. By contrast, mupirocin showed the highest logaritmic reduction of S. aureus. Conclusions: MB-aPDT and mupirocin treatments are effective in a murine superficial skin infection model of S. aureus. One session of MB-aPDT was the best option for clinical wound healing and cosmetic results. The addition of mupirocin to MB-aPDT treatment improved antimicrobial activity; however, it did not enhance wound healing. No synergistic antibacterial effects were detected.